Niveles de ventas en el Comercial “Don Jorge” ubicado en la ciudad de Babahoyo, periodo 2022. - Acurio Meléndez, Shirley Yadira (2023)
In the present work that was carried out in the Comercial Don Jorge, in the city of Babahoyo, Province of Los Ríos, within the market it is dedicated to the sale of basic necessities at retail. The objective of this case study was to compare the sales levels of the commercial Don Jorge in the years 2021, 2022 and identify the weak points of the company, and the degree of recognition of the commercial Don Jorge was determined, which was linked to the administrative, financial, tax, and audit management research line is part of the marketing and commercialization subline because they are dedicated to the activity of offering products to the market for their income. The methodology that was used in the investigation is the deductive method with a quantitative approach, with it it was possible to know more in depth about the strengths and weaknesses, allowing the analysis of the characteristics that were able to solve, optimize and reinforce the internal processes of the commercial Don Jorge, allowed the following results to be obtained: internally, the company has an average rating of 3.30 for the evaluation of internal factors, which indicates that if it is handling internal problems correctly, the The level of recognition of the commercial Don Jorge is good, but the problems that have been raised in this investigation must be taken into account.